A hardware and software integration approach for development of a non-invasive condition monitoring systems for motor-coupled gears faults diagnosis - Irfan, M. (Springer Verlag, 2017)
A non-invasive condition monitoring system for diagnosis of faults is vital for induction motors to operate safely and reliably. The currently used invasive techniques need direct access to the motor to collect and analyze data. Furthermore, the sensors used in invasive techniques are relatively expensive. This paper presents the development of hardware and software integrations for non-invasive diagnostic system to monitor specifically motor-coupled gear defects. The proposed system employs instantaneous power analysis, a unique technique for diagnostic condition monitoring which allows real-time non-stop tracking as well as assesses the severity of the defects. This technique can be adopted for decision-making that is not only fast but reliable. The severity of different gear defects have been studied experimentally, and the results were analyzed. The effectiveness of the proposed method has been verified through experimentation from the actual hardware implementation through the system-design platform and development environment software tool, LabVIEW. © Springer Nature Singapore Pte Ltd. 2017.